Pengaruh Orientasi Profesional terhadap Konflik Peran: Partisipasi Anggaran dan Orientasi Tujuan Sistem sebagai Variabel Moderating (Studi pada Kantor Akuntan Publik di DKI Jakarta dan Bandung) - Lidya Agustina; Christine Dwi Karya Susilawati (Jurnal Akuntansi, 2009)
The purpose of this research is to analyze and examine the hypothesis effect of professional orientation on role conflict with budgetary participation and system goal orientation as a moderating variabel. The respondent of this research is auditor in manager and partner level, who are working in accounting firm in DKI Jakarta and Bandung. The method that is used in this research is causal. Sampling technique employed in this research is simple random sampling. Cross-sectional is also used in this research. It is also using simple regression analysis to exemine the effect of professional orientation on role conflict, and moderated regression analysis to exemine the effect with moderating variable. The result of this research shows that professional orientation give effect to role conflict. Budgetary participation gives a positive effect to professional orientation with role conflict correlation. Altough system goal orientation gives a negative effect to professional orientation with role conflict correlation. Keywords: professional orientation, budgetary participation, system goal orientation, role conflict.